Carcass wrote:
If 4(r – s) = –2, then what is r, in terms of s ?
A) \(\frac{-8}{2}\)
B) \(s - \frac{1}{2}\)
C) \(s - \frac{3}{2}\)
D) \(s + 2\)
E) \(2s\)
Given: 4(r – s) = –2
[solve for r]Expand: 4r - 4s = -2
Add 4s to both sides: 4r = -2 + 4s
Rewrite right side: 4r = 4s - 2
Divide both sides by 4 to get: r = (4s - 2)/4
Check answer choices....not there. Looks like they want us to simplify.
We can use a nice rule that says (a - b)/c = a/c - b/c
So, (4s - 2)/4 = 4s/4 - 2/4
= s - 1/2
Answer:
Cheers,
Brent